Gas-Producing Renal Infection Presenting as Pneumaturia: A Case Report - Youssef S. Tanagho; Jonathan M. Mobley; Brian M. Benway; Alana C. Desai (Case Reports in Medicine)
We present a case of persistent pneumaturia of one-year duration in a fifty-five-year-old male with a history of spinal cord injury. The evaluation demonstrated gas throughout the collecting system attributable to a urinary tract infection with a gas-forming organism, Klebsiella pneumoniae.